FA-10 Sperm Freezability of Various Breed of Bulls at Lembang AI Center - Zulfi Nur Amrina Rosyada; Tri Harsi; Bambang Purwantara (Hemera Zoa, 2018)
Currently, artificial insemination (AI) techniques using cryopreserved semen have been widely used to improve the genetic potential of livestock species. Semen at the Lembang AI Center usually collected by artificial vagina (AV) then the semen should be evaluated to get the good quality of spermatozoa for the freezing process. Several efforts are being made to improve the quality of frozen semen for AI so as to get the most out of this technology. But there are certain obstacles in this path to achieve breeding goals. The trend now is to design procedures or refine methodologies so as to maximize the production of good quality semen without discarding too many poor quality ejaculates. Therefore, to minimize the poor or discarded spermatozoa used in the cryopreservation process, this study might elaborate more about the influencing factors.